Video Learning Oriented to the Value of Caring for the Environment - Aprilianingsih, Ni Komang Ary Sri; Asril, Nice Maylani (MIMBAR PGSD Undiksha, 2022)
The development of technological flows in the era of globalization requires teachers to take advantage of various technological advances to improve student learning outcomes. It is just that the reality on the ground shows that teachers still find it difficult to develop media related to the use of technology. This study aims to develop a learning video oriented to the value of caring for the environment in the fifth-grade science content of Elementary School. This research belongs to the type of development research using the ADDIE development model. The research subjects are two material experts, two learning design experts, and two learning media experts. The test subjects were two practitioners/teachers and ten fifth-grade students. The data collection methods used are observation, interviews, and questionnaires, with the data collection instrument as a rating scale. The analytical technique used is descriptive qualitative and quantitative analysis. The results showed that the assessment given by the subject content expert was 3.84 (very good), the instructional media expert was 3.83 (very good), and the learning design expert was 3.86 (very good). The results of the practitioner's response test are 3.60 (very good), and the student response is 3.76 (very good). So based on these results, it can be concluded that the value-oriented learning media for environmental care characters in the science content of the water cycle material for class V Elementary School is feasible to be developed and used in the learning process.